Coccinellidae on native and introduced spruce in central Europe: conservation implications in urban areas - Jauschová, Terézia; Sarvašová, Lenka; Zach, Peter; Saniga, Miroslav; Martinková, Zdenka; Honěk, Alois; Skuhrovec, Jiří; Holecová, Milada; Kulfan, Ján (Frontiers in Ecology and Evolution, 2024)
The abundance and species composition of adult ladybird communities (Coleoptera: Coccinellidae) were investigated on two congeneric trees, native Norway spruce (Picea abies) and the introduced blue spruce (Picea pungens), at four locations in Slovakia (central Europe). For two years (2021–2022), coccinellid adults were sampled using a standard method involving beating branches at monthly intervals from April to November. Although the species composition of the communities on both spruce species was similar, the abundance of the entire coccinellid community as well as the abundance of individual species was significantly greater on Norway spruce than on blue spruce. With the current decline of Norway spruce as a result of several negative factors, blue spruce has emerged as a suitable substitute host plant for coccinellid communities in urban areas.